The Effect of Gargling Green Meniran Decoction on Bacterial Total Plate Count in Oral Cavity - Dhiya, Salsabila Shafa; Dewangga, Vector Stephen (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Green meniran (Phyllanthus niruri Linn.) is a herb that grows wild and has antibacterial properties such as flavonoids, alkaloids, tannins, and saponins that can kill bacteria. Oral hygiene is an action to improve dental and oral hygiene, one of which is by gargling. This study is conduct to see the effect of green meniran decoction as a herbal mouthwash on the Total Plate Count (TPC) of bacteria in the oral cavity, then it will be compared with a mouthwash containing 0.2% chlorhexidine which is already known as a mouthwash that has the potential to maintain oral health. The type of research is experimental analysis using 3 groups, negative control, treatment and positive control with pre and post group design. The results of the study showed that a 100% concentration of green meniran decoction can reduce the number of bacterial colonies in the oral cavity and can be used as an alternative as a natural-based mouthwash.